The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4025/revcivet.v7i1.55490
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Coronaviruses in Neotropical Primates: A New Threat?

Abstract: Anthropogenic activities are the main reason for the current alarming conservation status of non-human primates (NHP) worldwide, and also lead to habitat-sharing, facilitating human-NHP (interspecific) viral transmission. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the ongoing COVID-19 pandemic, is well-known for its large genome plasticity and spike proteins (S proteins) highly adaptable to human receptor angiotensin-converting enzyme-2 (ACE2). NHP have been used as model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition, experimental infection studies have reported susceptibility of several animals such as ferrets, bats, hamsters (Shi et al 2020 ; Imai et al 2020 ) and mainly Old World NHPs (Zheng et al 2020 ; Lu et al 2020 ). As a result, concern about the possibility of SARS-CoV-2 spillback for Neotropical Primates—as happened with YFV in the last century and probably with ZIKA in the last decade—has grown (Terzian et al 2018 ; Yunes Guimarães et al 2020 ). However, the only report of experimental infection in a neotropical NHP published to date examined the dynamics of SARS-CoV-2 infection in Callithrix jacchus , the common marmoset.…”
mentioning
confidence: 99%
“…In addition, experimental infection studies have reported susceptibility of several animals such as ferrets, bats, hamsters (Shi et al 2020 ; Imai et al 2020 ) and mainly Old World NHPs (Zheng et al 2020 ; Lu et al 2020 ). As a result, concern about the possibility of SARS-CoV-2 spillback for Neotropical Primates—as happened with YFV in the last century and probably with ZIKA in the last decade—has grown (Terzian et al 2018 ; Yunes Guimarães et al 2020 ). However, the only report of experimental infection in a neotropical NHP published to date examined the dynamics of SARS-CoV-2 infection in Callithrix jacchus , the common marmoset.…”
mentioning
confidence: 99%
“…In addition, experimental infection studies have reported susceptibility of several animals such as ferrets, bat, hamsters (Shi et al 2020;Imai et al 2020), and mainly Old World NHPs (Zheng et al 2020;Lu et al 2020). As a result, concern about the SARS-CoV-2 spillback for Neotropical Primates -as happened with YFV in the last century and probably with ZIKA in the last decadehas grown (Terzian et al 2018;Yunes Guimarães et al 2020).…”
mentioning
confidence: 99%